Remittances, ICT and pension income coverage: The international evidence - David Adeabah; Simplice Asongu; Charles Andoh (African Governance and Development Institute (AGDI), 2020)
This study examines the impact of remittances and information and communication technology (ICT) on pension at the country level. Our empirical evidence, based on data from 96 countries, indicate a significant non-linearity between remittances, ICT and pension income coverage. First, we find a convex relation between remittances and pension income coverage, indicating that increases in remittance, initially decreases pension income coverage, but as remittance increases beyond a certain point, so too does pension income coverage. This inflection point, where the effect of remittances turns from negative to positive, is estimated to be around 3.09% of GDP. Second, we document a concave relationship between ICT (i.e. mobile subscription and internet penetration) and pension income coverage. An increase in ICT results in increased pension income coverage. However, when ICT reaches a certain point, any further increase is associated with lower pension income coverage. The estimated optimal point is found to be around 140.14 subscriptions (per 100 people) for mobile phone and 27.93 (per 100 people) for internet penetration, respectively. Other implications are discussed.
Keywords: 330; Pension income coverage; Remittances; Mobile subscription; Internet penetration; ICT